2018
DOI: 10.1038/s41598-018-25679-z
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning model with human cognitive biases capable of learning from small and biased datasets

Abstract: Human learners can generalize a new concept from a small number of samples. In contrast, conventional machine learning methods require large amounts of data to address the same types of problems. Humans have cognitive biases that promote fast learning. Here, we developed a method to reduce the gap between human beings and machines in this type of inference by utilizing cognitive biases. We implemented a human cognitive model into machine learning algorithms and compared their performance with the currently mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…For example, machine learning models with human cognitive biases are already capable of learning from small and biased datasets [44]. This process reminds me of the role of the Student test in relation to frequentist ideas, always requesting large sets of data until the creation of the t-test, something that could be applied now in the context of machine learning.…”
Section: Extending Bad And/or Good Human Cognitive Skills Through DLmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, machine learning models with human cognitive biases are already capable of learning from small and biased datasets [44]. This process reminds me of the role of the Student test in relation to frequentist ideas, always requesting large sets of data until the creation of the t-test, something that could be applied now in the context of machine learning.…”
Section: Extending Bad And/or Good Human Cognitive Skills Through DLmentioning
confidence: 99%
“…In [44], the authors developed a method to reduce the inferential gap between human beings and machines by utilizing cognitive biases. They implemented a human cognitive model into machine learning algorithms and compared their performance with the currently most popular methods, naïve Bayes, support vector machine, neural networks, logistic regression, and random forests.…”
Section: Extending Bad And/or Good Human Cognitive Skills Through DLmentioning
confidence: 99%
“…For example, machine learning models with human cognitive biases are already capable of learning from small and biased datasets [63]. This process reminds the role of Student test in relation to frequentist ideas, always requesting large sets of data until the creation of the t-test, but now in the context of machine learning.…”
Section: Extending Bad And/or Good Human Cognitive Skills Through DLmentioning
confidence: 99%
“…In [63] boost the potentiality of DL, diminishing the computational power of the systems as well as adding new heuristic approaches to information analysis [35], [65]- [67].…”
Section: Extending Bad And/or Good Human Cognitive Skills Through DLmentioning
confidence: 99%
“…The purposes of our model are to improve classification accuracy with a small number of biased training examples and to create a new NN framework which utilizes human cognitive biases. Previous studies such as [17], [30], [31] showed the effectiveness of human cognitive biases for machine learning tasks, especially when the small and biased number of examples were given to the model. In our model, NN with LS can omit nodes and "revive" them according to the status of the network.…”
Section: Introductionmentioning
confidence: 99%